ANALYSIS OF THE PHYSICAL FITNESS OF THE PROFESSIONAL SOCCER PLAYERS OF THE ESPORTE CLUBE FLAMENGO - PI (ECF) IN 2011 SEASON. (Fiep Bulletin - online, 2012)
Present study aimed at evaluating the level of physical fitness of professional soccer squad Sport Club Flamengo - PI (ECF). The sample consisted of 30 athletes who underwent fitness tests at the beginning of the 2011 season. All subjects were male, had an average age of 21.1 +4.1 years, height 177.9 +7.4 cm and body mass 70.9 +7.6 kg. The battery of tests used at the end of the pre-season 2011 were: Illinois, Cooper and Rast Test 2400m 35m. The players have an average of 16.99 seconds at +0.4 agility test, Pikes traveled 35 meters in 5.63 seconds and +0.56 Cooper performed the test on 2400m 9.32 +0.07 minutes. The data analysis found that, in absolute terms, the athletes of the ECF produced unsatisfactory results in all the physical tests, so would not be physically ready to compete at national games.
Keywords: soccer; physical fitness and tests